Pengaruh Good Coorporate Governance, Manajemen Risiko, Dan Intelllectual Capital Terhadap Kinerja Keuangan (Studi Pada Perusahaan Sektor Perbankan Yang Terdaftar di BEI Periode 2022-2024) - Hazlina Rahmanda Nursanti; Jeni Susyanti; Mohamad Bastomi (UNIVERSITAS ISLAM MALANG, 2026)
Abstract This study analyzes the effect of good corporate governance (GCG), risk management, and intellectual capital on the financial performance of banks listed on the Indonesia Stock Exchange (IDX) for the 2022-2024 period. The sample was selected using purposive sampling, and the data were analyzed using multiple linear regression. GCG was measured using the Corporate Governance Performance Indicator (CGPI score), risk management was proxied by Non-Performing Loan (NPL), intellectual capital was measured by Value Added Intellectual Coefficient (VAIC), and financial performance was proxied by Return on Equity (ROE). The results show that GCG and risk management have a significant effect on financial performance, while intellectual capital has an insignificant effect. These findings indicate that good governance and effective credit risk control effectively drive profitability, but investments in intellectual capital require time to be converted into improved performance. The implications of this study are beneficial for investors, bank management, and regulators. Keywords: Good Corporate Governance, Risk Management, Intellectual Capital, Financial Performance, Banking